Homoarginine, heart failure, and sudden cardiac death in haemodialysis patients - Drechsler, Christiane; Meinitzer, Andreas; Pilz, Stefan; Krane, Vera; Tomaschitz, Andreas; Ritz, Eberhard; März, Winfried; Wanner, Christoph (European journal of heart failure, 2011)
Aims Sudden cardiac death (SCD) is a major contributor to the excess mortality of patients on maintenance dialysis. Homoarginine deficiency may lead to decreased nitric oxide availability and endothelial dysfunction. Based on this rationale we assessed whether homoarginine deficiency is a risk factor for SCD in dialysis patients. Methods and results This study examined the association of homoarginine with cardiovascular outcomes in 1255 diabetic haemodialysis patients from the German diabetes and dialysis study. During a median of 4 years of follow-up, hazard ratios (HR) (95% CI) for reaching the following pre-specified, adjudicated endpoints were determined: SCD, myocardial infarction, stroke, death due to heart failure, and combined cardiovascular events. There was a strong association of low homoarginine concentrations with the presence of congestive heart failure and left ventricular hypertrophy as well as increased levels of brain natriuretic peptide. Per unit decrease in homoarginine, the risk of SCD increased three-fold (HR 3.1, 95% CI 2.0-4.9), attenuating slightly in multivariate models (HR 2.4; 95% CI 1.5-3.9). Patients in the lowest homoarginine quintile experienced a more than two-fold increased risk of SCD, and more than three-fold increased risk of heart failure death than patients in the highest quintile, which accounted for the high incidence of combined cardiovascular events. Low homoarginine showed a trend towards increased risk of stroke, however, myocardial infarction was not meaningfully affected. Conclusion Low homoarginine is a strong risk factor for SCD and death due to heart failure in haemodialysis patients. Further studies are needed to elucidate the underlying mechanisms, offering the potential to develop new interventional strategies.
First published: 18 February 2014
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 21.06.2022